Awareness-Usage Gap of Reference Management Tools Among Social Science Researchers in Universities of Bihar: A Study (LIS TODAY, 2026)
This study investigates the awareness, usage patterns, and barriers to adopting Reference Management Tools (RMTs) among PhD research scholars in the Social Science Faculty of five state government universities in Bihar, India. Utilizing a mixed methods design, a survey was conducted with 267 scholars, yielding an 89% response rate. Findings reveal a critical paradox: while 88.39% of scholars are aware of RMTs, only 44.07% are active users. The primary barriers identified include a lack of training (73.39%) and perceived tool complexity (65.46%). Usage is highly irregular, with 65.57% utilizing tools only during the final thesis or paper writing phase. The study concludes that institutional efforts must shift from basic awareness to mandatory, practical training to bridge the significant awareness-adoption gap.
Keywords: :Reference Management Tools (RMTs); Awareness Usage Gap; Mendeley; Zotero; EndNote; PhD Research Scholars; Social Science Research; Digital Research Workflow; Bibliographic Management; Higher Education in Bihar; PhD Research Scholars of Bihar; Social Science Research Scholars of Bihar; Reference and Bibliographic Writing.